2004
DOI: 10.5962/bhl.title.113962
|View full text |Cite
|
Sign up to set email alerts
|

Methods for controlling depredation on piping plovers in Alberta : a literature review and synthesis /

Abstract: The piping plover (Charadrius melodus) is listed as Endangered under Alberta's Wildlife Act, and in most otherjurisdictions in North America (Alberta Piping Plover Recovery Team 2002). Poor productivity as a result ofpredation of eggs and chicks has been identified as the greatest source ofreproductive failure for piping plovers in Alberta. The Alberta Piping Plover Recovery Plan 2002-2004 identified a need for increased predator management in order to boost reproductive success (Alberta Piping Plover Recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…For example, we spaced upland waterfowl points 121 m apart at an agl 46 m (as described above) and spaced passerine point samples 30.5 m apart at an agl of 23 m (ground sampling distance of 2 cm/pixel and four times the resolution). Modifications were also made at piping plover nest sites to account for the presence of predator exclosure cages (Schemlzeisen et al 2004). At the piping plover study site search methodology focused on collecting detailed imagery at altitudes from 30 m to 15 m above the known nests while performing the search transect adjacent to the cages to look for other nests.…”
Section: Nest Searching Methodsmentioning
confidence: 99%
“…For example, we spaced upland waterfowl points 121 m apart at an agl 46 m (as described above) and spaced passerine point samples 30.5 m apart at an agl of 23 m (ground sampling distance of 2 cm/pixel and four times the resolution). Modifications were also made at piping plover nest sites to account for the presence of predator exclosure cages (Schemlzeisen et al 2004). At the piping plover study site search methodology focused on collecting detailed imagery at altitudes from 30 m to 15 m above the known nests while performing the search transect adjacent to the cages to look for other nests.…”
Section: Nest Searching Methodsmentioning
confidence: 99%
“…2. Employ and expand, where possible, the use of specific predator deterrence measures recommended by Schmelzeisen et al (2004) to increase plover productivity and survivorship.…”
Section: Action Planmentioning
confidence: 99%
“…However, mink, red fox, peregrine falcons, red-tailed hawks and great homed owls and merlins are known to be responsible for adult predation (Haig 1992, Michaud and Prescott 1999, Murphy et al 2003. Management tools available to decrease predation of nests and/or adults include predator removal, destruction of stick nests during the nonbreeding season, erection of electric fencing and the use of predator exclosures around nests (Schmelzeisen et al 2004). A predator exclosure project initiated in Alberta in 1996 showed that fledging success rates of exclosed nests were more than double those of unprotected nests (Richardson 1999).…”
Section: Predationmentioning
confidence: 99%
“…2. Employ and expand, were possible, the use of specific predator deterrence measures recommended by Schmelzeisen et al (2004) to increase plover productivity and survivorship.…”
Section: Productivity Enhancementmentioning
confidence: 99%